Involving STEM Students in Critical Analysis Tasks on the Processes of Modifying Optical Properties of Materials - Bilad, Muhammad Roil; Doyan, Aris (International Journal of Essential Competencies in Education, 2023)
The present study aimed to train STEM students' critical analysis skills in the material modification process. The optical properties of the mixed polymer materials (polyvinyl alcohol, methylene blue dye, and trichloroacetic acid) were modified using gamma (?) radiation techniques. The fabrication process of polymer films blend irradiated with ? rays was carried out by the lecturer, including absorbance measurements. The task assigned to the STEM students was to critically analyze the optical characteristics of the irradiated polymer films. The method was divided into two sections: 1) the fabrication of ?-irradiated polymer films, which involved preparation, radiation, and absorbance measurement of the polymer film blend, and 2) the assessment of critical analysis skills in STEM students, which was based on a portfolio of critical analysis tasks. The results of the analysis showed changes in the physical properties and optical characteristics of the polymer film blend, including its potential application as ? radiation dosimetry. The results of the critical analysis task indicated that STEM students were able to complete the task effectively. Overall, the findings of this study demonstrate the success of STEM students in conducting critical analysis of the optical characteristics of polymer films blends irradiated by ?-rays.